The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2147/jn.s77813
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous spinal stimulation as a therapeutic strategy for spinal cord injury: state of the art

Abstract: Treatments for spinal cord injury (SCI) still have limited effects. Electrical stimulation might facilitate plastic changes in affected spinal circuitries that may be beneficial in improving motor function and spasticity or SCI-related neuropathic pain. Based on available animal and clinical evidence, we critically reviewed the physiological basis and therapeutic action of transcutaneous spinal cord stimulation in SCI. We analyzed the literature published on PubMed to date, looking for the role of three main n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 56 publications
(74 reference statements)
0
23
0
Order By: Relevance
“…Neuromodulation of the spinal cord by means of non-invasive transcutaneous (tSCS) and implanted epidural (eSCS) spinal cord stimulation may improve sensorimotor rehabilitation after spinal cord injury (SCI) [1][2][3][4]. However, developing an optimal treatment approach requires taking advantage of the intrinsic ability of the spinal circuits by facilitating preserved sensorimotor pathways that could drive spinal plasticity [5]. The influence of spinal cord stimulation (SCS) does not necessarily depend on the nature of the neurological disorder, but on the operational and functional status of residual neural networks [6].…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulation of the spinal cord by means of non-invasive transcutaneous (tSCS) and implanted epidural (eSCS) spinal cord stimulation may improve sensorimotor rehabilitation after spinal cord injury (SCI) [1][2][3][4]. However, developing an optimal treatment approach requires taking advantage of the intrinsic ability of the spinal circuits by facilitating preserved sensorimotor pathways that could drive spinal plasticity [5]. The influence of spinal cord stimulation (SCS) does not necessarily depend on the nature of the neurological disorder, but on the operational and functional status of residual neural networks [6].…”
Section: Introductionmentioning
confidence: 99%
“…Supported by electrical current modelling ( Parazzini et al , 2014 ; Fregni et al , 2015 ; Fiocchi et al , 2016 ; Kuck et al , 2017 ), preclinical ( Zaghloul, 2014 , 2016 ; Weiguo et al , 2015 ), neurophysiologic ( Cogiamanian et al , 2012 ; Priori et al , 2014 ) and neuroimaging studies ( Schweizer et al , 2017 ), a growing body of literature suggests that tsDCS can modulate activity at multiple levels of the central nervous system, including the segmental spinal cord ( Winkler et al , 2010 ; Lamy et al , 2012 ; Hubli et al , 2013 ), ascending lemniscal and nociceptive pathways ( Cogiamanian et al , 2008 ; Cogiamanian et al , 2011 ; Truini et al , 2011 ), as well as cortical regions ( Bocci et al , 2014 , 2015 a , b , c ; Marangolo et al , 2017 ; Schweizer et al , 2017 ). In addition, a recent proof-of-concept study from our group, in young and neurologically intact individuals, found that anodal tsDCS applied over the lower thoracic region (T-11) concurrently with BLTT, increased the acquisition rate and retention of backward walking speed up to 2 weeks post-training ( Awosika et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given these findings, previous modeling and electrophysiological studies attempted to modulate subcortical function using DCS applied over the spine (tsDCS). These studies demonstrated that tsDCS could indeed modulate spinal cord function (17,19,20,29,31,32,59,60), raising the question whether it could also influence locomotor behavior. In this investigation, we used the same montage and stimulating parameters reported to modulate electrophysiological measures of spinal cord function to address a novel question: could tsDCS modulate locomotor behavior in the form of learning a novel backward task of relevance in sports medicine and neurorehabilitation (61)(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…provided mechanistic foundation to these empirical findings (29)(30)(31)(32). It is then possible that tsDCS could also influence locomotor learning.…”
Section: Introductionmentioning
confidence: 88%